2018
DOI: 10.1104/pp.18.00610
|View full text |Cite
|
Sign up to set email alerts
|

MtNODULE ROOT1 and MtNODULE ROOT2 Are Essential for Indeterminate Nodule Identity

Abstract: One-sentence summary: 40The loss-of-function of MtNOOT1 and MtNOOT2 leads to the complete loss of nodule identity, prevents 41 the symbiotic process, and results in the absence of nitrogen fixation in Medicago truncatula. 56VZ, SC, GEDO, and PR analyzed the data. KM, KS and PR wrote the article. 58This work was supported by the CNRS, by the grants ANR SVSE 6.2010.1 (LEGUMICS) and ANR-14- 62Agriculture (Dufrenoy Grant, 2011). This work has benefited from the facilities and expertise of the IMAGIF 63Cell Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 86 publications
(38 reference statements)
5
56
0
Order By: Relevance
“…A number of TFs were demonstrated to play a crucial role in nodule development through genetic evidence from model legumes (4, 30). These include NODULE INCEPTION ( NIN ) (RWP-RK family; (31), NODULATION SIGNALING PATHWAY1 and 2 (NSP1 and NSP2; GRAS domain proteins), Nuclear Factor Y (NF-YA1; (32)), E thylene Response Factors R equired for N odulation (ERN1 and ERN2; AP2/ERF family; (33)), and CYCLOPS (coiled-coil domain protein) (3437).…”
Section: Resultsmentioning
confidence: 99%
“…A number of TFs were demonstrated to play a crucial role in nodule development through genetic evidence from model legumes (4, 30). These include NODULE INCEPTION ( NIN ) (RWP-RK family; (31), NODULATION SIGNALING PATHWAY1 and 2 (NSP1 and NSP2; GRAS domain proteins), Nuclear Factor Y (NF-YA1; (32)), E thylene Response Factors R equired for N odulation (ERN1 and ERN2; AP2/ERF family; (33)), and CYCLOPS (coiled-coil domain protein) (3437).…”
Section: Resultsmentioning
confidence: 99%
“…Mtnoot2 mutants do not form nodules with root outgrowths. However, the occurrence of nodule roots increases in Mtnoot1 Mtnoot2 double mutants (Magne et al, 2018a). Therefore, MtNOOT2 also plays a role in maintaining nodule organ identity.…”
Section: " "mentioning
confidence: 98%
“…To investigate this notion, we searched for a legume mutant with the ability to form roots at the apex of nodules. We selected a legume with a mutation in the NOOT/NBCL gene, which can form functional nodules and, like some actinorhizal-type nodules, can form a root at their apex (Couzigou et al 2012;Magne et al 2018a). To determine if the vascular bundles in noot/nbcl mutant nodules have a similar ontogeny to that observed in actinorhizal-type nodules, we studied nodule development in the Medicago Mtnoot1 knockout mutant.…”
Section: Nodule Ontogenymentioning
confidence: 99%
“…Zmliguleless narrow (Zmlgn), encoding a kinase likely acting upstream of Zmlg1 and Zmlg2, is also required for ligule and auricle development (Moon et al, 2013). The NBCL genes encode BTB/POZ and ankyrin repeat containing proteins that can act as E3 ubiquitin ligases but that are also able to interact with themselves and with TGA bZIP TFs (Zhang et al, 1999;Despr es et al, 2000;Zhou et al, 2000;Despr es et al, 2003;Hepworth et al, 2005;Boyle et al, 2009;Wu et al, 2012;Zhang et al, 2017;Magne et al, 2018b;Wang et al, 2019). ZmLG2 is orthologous to a TGA bZIP TF encoded by the Bra-di2g55567 locus in B. distachyon (similarity 87.3%, identity 78.1%).…”
Section: Cul4 Is Essential For Ligule and Auricle Developmentmentioning
confidence: 99%
“…Pictures of whole organs were acquired using a Nikon AZ100 Microscope (Nikon, http://www.nikoninstruments.com/). Technovit sections were performed as described in Magne et al (2018b), sections were observed with a microscope (BX53; Olympus, https:// www.olympus-lifescience.com/) and pictures acquired using cell-Sens Standard software (Olympus).…”
Section: Imaging Light Microscopy and Sample Preparationmentioning
confidence: 99%